Flood Fill and Scanline Fill Algorithm Optimization to Improve Design and Animation Application Performance - Sholahuddin, Fakhri; Sutabri, Tata (Yayasan Rumah Ilmu Professor, 2025)
Flood and Scanline Fill algorithms are two primary methods in the color-filling process in design and animation applications. However, limitations in computational efficiency often cause long rendering times, especially for high-resolution images and complex areas. This study aims to optimize both algorithms by implementing parallel processing using multi-threading technology and GPU-based processing. This implementation is expected to improve color filling performance compared to conventional methods significantly. Testing was carried out by comparing the execution time of the algorithm before and after optimization in various usage scenarios. The results showed that the parallel processing technique accelerated the color-filling process by up to 60% under certain conditions. Thus, this approach improves the efficiency of design and animation applications, especially in real-time rendering.